Comparison of outcomes following vaginal natural orifice transluminal endoscopic surgery and laparoendoscopic single-site surgery in benign hysterectomy: A systematic review and meta-analysis - Avir Sarkar; P Sivaranjani; Rinchen Zangmo; Kallol Kumar Roy; Maninder Kaur Ghotra; Radha Rani Seelam; Shivam Pandey (Wolters Kluwer Medknow Publications, 2023)
Gradually increasing interest in laparoscopic surgeries has led to the advent of various lesser invasive techniques in the form of vaginal natural orifice transluminal endoscopic surgery (vNOTES) and laparoendoscopic single-site (LESS) surgery. Very few studies have analyzed the advantages and disadvantages of vNOTES over LESS surgeries in hysterectomy. After a comprehensive search, full texts of relevant manuscripts were obtained to assess eligibility for recruitment. A comprehensive meta-analysis was subsequently performed to compare the outcomes of vNOTES and LESS in hysterectomy, and forest plots were constructed. Four articles were rendered for review (three retrospective cohort studies and one randomized controlled trial). Three studies showed lesser postoperative pain in vNOTES compared to LESS. In one study, postoperative vaginal pain was higher in vNOTES due to additional suture between uterine artery and vaginal wall. The meta-analysis concluded that vNOTES could be better alternative to LESS hysterectomies. However, further large multicentric randomized trials are required for the standardization of the surgical method.